tert-Butyl Hypochlorite: A Reagent for the Synthesis of Chlorinated Oxindole and Indole Derivatives - Chun-Yan Liu; Xia Chen; Hai-Long Liu; Nan Wang; Xiao-Yu Zhou (Molecules)
tert-Butyl hypochlorite was employed as a versatile reagent for chlorooxidation of indoles, chlorination of 2-oxindoles, and decarboxylative chlorination of the indole-2-carboxylic acids. Four types of products including 2-chloro-3-oxindoles, 2,2-dichloro-3-oxindoles, 3,3-dichloro-2-oxindoles, and 2,3-dichloroindoles could be selectively obtained in moderate to excellent yields by switching the substrates. Various synthetically useful functional groups, such as halogen atoms, cyano, nitro, and methoxycarbonyl groups, remain intact during the reactions. Notable features of the approach include the universality of the starting materials, the mild reaction conditions, and the experimental simplicity.